Euro Area Policies : 2013 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2013)
This staff paper on euro area policy 2013 Article IV Consultation discusses economic development and policies. Severe market stresses have subsided, although private borrowing costs have remained too high in the periphery. In these economies, sovereign borrowing costs have declined from unsustainable levels. This has led to slightly lower private borrowing costs, spurring bond issuance among some banks, and firms. Capital flight has gradually eased, bank deposits have stabilized, and Target 2 imbalances have narrowed. This has contributed to some early repayment of official liquidity support by stronger banks, though largely from core countries. Still, periphery bank risks are significantly higher than in the core.